Heterogeneous RNA editing and influence of ADAR2 on mesothelioma chemoresistance and the tumor microenvironment. Issue 22 (31st October 2022) - Hariharan, Ananya; Qi, Weihong; Rehrauer, Hubert; Wu, Licun; Ronner, Manuel; Wipplinger, Martin; Kresoja‐Rakic, Jelena; Sun, Suna; Oton‐Gonzalez, Lucia; Sculco, Marika; Serre‐Beinier, Véronique; Meiller, Clément; et al.
Abstract : We previously observed increased levels of adenosine‐deaminase‐acting‐on‐dsRNA (Adar)‐dependent RNA editing during mesothelioma development in mice exposed to asbestos. The aim of this study was to characterize and assess the role of ADAR‐dependent RNA editing in mesothelioma. We found that tumors and mesothelioma primary cultures have higher ADAR‐mediated RNA editing compared to mesothelial cells. Unsupervised clustering of editing in different genomic regions revealed heterogeneity between tumor samples as well as mesothelioma primary cultures. ADAR2 expression levels are higher in BRCA1‐associated protein 1 wild‐type tumors, with corresponding changes in RNA editing in transcripts and 3'UTR. ADAR2 knockdown and rescue models indicated a role in cell proliferation, altered cell cycle, increased sensitivity to antifolate treatment, and type‐1 interferon signaling upregulation, leading to changes in the microenvironment in vivo . Our data indicate that RNA editing contributes to mesothelioma heterogeneity and highlights an important role of ADAR2 not only in growth regulation in mesothelioma but also in chemotherapy response, in addition to regulating inflammatory response downstream of sensing nucleic acid structures. Abstract : Human mesothelioma has increased A‐to‐I RNA editing compared to normal mesothelium. Disrupted Hippo pathway and wild‐type BAP1 are associated with increased ADAR2 expression. This results in (a) increased cell growth, (b) pemetrexed resistance, via changes in expression of pemetrexed targets and in alternate splicing, and (c) the blockade of interferon signaling, which alters tumor microenvironment in vivo . Created with BioRender.com